Manajemen Laba Dan Kecurangan Laporan Keuangan: Industri Pariwisata Dan Rekreasi Di Indonesia - Mimelientesa Irman; Silfi Putri Anjani; Yenny Wati (Universitas Muhammadiyah Malang, 2023)
Purpose: The objective of this study was to determine the impact of financial target, financial leverage, financial stability, and company size on earnings management and their effect on financial reporting fraud in tourism and recreation industry companies traded on the Indonesia Stock Exchange for the 2017-2021 period. Methodology/approach: This study uses secondary data, namely data obtained indirectly. The sampling technique in this study used a purposive sampling technique. There were 90 observation samples of data obtained. The analytical method of this research uses descriptive analysis and several types of evaluation using SmartPLS software. Findings: From this reseaxch, it was concluded that only financial targets have a significant impact on earnings management and financial reporting fraud. Meanwhile, financial leverage, financial stability, and company size do not have a significant impact on earnings management and financial reporting fraud. Earnings management has no significant impact on financial reporting fraud. Practical implications: Investors can lessen the risk of poor firm performance by focusing not only on profit-oriented financial data, but also on other investment-related data. Originality/value: This research analyzes the most recently published concerns raised in the literature on fraud and earnings management. This study serves as a guideline for financial report readers when evaluating financial information and corporate performance.